Nutritional and sensory characteristics of developed wheat burger buns incorporated with different levels of steamed-squid (Loligo forbesii) powder - Ali, Rehab F. M.; El-Anany, Ayman M. (Frontiers in Nutrition, 2025)
IntroductionThe main aim of the present investigation was to determine the nutritional and sensory characteristics of wheat flour burger buns supplemented with different quantities of steamed squid powder (SSP).MethodsWheat flour was partially substituted with SSP at various proportions (0, 1, 2, 3, 4, and 5% w/w). The proximate composition and techno-functional features of wheat flour, SSP, and composite flours were investigated. Chemical composition, specific volume, amino acid profile, and sensory characteristics of developed burger buns were investigated to determine the most suitable levels of substitution.ResultsThe techno-functional characteristics of produced composite flours were significantly improved by inclusion different levels of SSP into wheat flour. The incorporation of SSP into burger buns significantly enhances protein content while reducing carbohydrate levels. The study indicates that as the percentage of SSP increases from 1 to 5%, the protein content of the buns increases correspondingly, with a maximum increase of 1.42 times at 5% SSP. Additionally, carbohydrate levels decrease from 82.06% in control samples to 76.16% with the highest SSP addition. However, the specific volume of the buns shows a decline at higher SSP concentrations, particularly at 4 and 5%, where volumes drop to 2.89 and 2.85 cm3 g−1, respectively. The incorporation of SSP into burger buns significantly enhances the nutritional profile, particularly in essential amino acids. While the total essential amino acids and specific amino acids like leucine, isoleucine, and valine exceed FAO/WHO requirements, lysine levels remain a concern, increasing only to 3.20 g per 100 g of protein, below the required 5.2 g. The sensory evaluation of these buns shows high acceptability, with scores between 8.38 and 8.61, indicating a positive consumer response. Originality/value—The incorporation of steamed squid powder (SSP) into burger buns has been shown to enhance both nutritional and sensory properties, particularly when substituting 1–3% of wheat flour with SSP. This approach aligns with trends in food innovation aimed at improving health benefits while maintaining consumer acceptance.